PENERAPAN PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERBANDINGAN - Sri Wahyuni; Gandung Sugita; Muh. Rizal (Universitas Tadulako, 2021)
The purpose of this study is describe the application of realistic mathematical approaches on the cooperative learning model type Student Teams Achievement Division (STAD) to improve student learning outcomes in material VIIA MTs Negeri 1 Donggala. This type of research is classroom action research (CAR) and the design uses the Kemmis and Mc models. Taggart, with its stages namely : planning, implementing action, observing and reflecting. The subjects werw all studens of class VIIA, totaling 28 students. The study was conducted in two cycles. Based on the results of the final action test, the percentage of classical completeness of students in the first cycle was 55,55% and the percentage of classical completeness of students in the observations if the teachers and students in the first cycle were in the good category and in the second cycle were very good category. From the research results obtained it can be concluded that learning by applying a realistic mathematical approach to the cooperative learning model type student teams achievement ivision can improve stud ent learning outcomes in comparison material in class VIIA MTs Negeri 1 Donggala, by following the steps (1) the phase of accomplishing objectives and motivating, (2) the phase of presenting or conveying information (3) the phase of organizing students into study groups, (4) the phase of guiding work and study groups, (4) the phase of guiding work and study groups and (5) the evaluation phase.